The importance of the disease process and disease-modifying antirheumatic drug treatment in the development of septic arthritis in patients with rheumatoid arthritis. - Edwards, C; Cooper, C; Fisher, D; Field, M; van Staa, T; Arden, N (2007)
OBJECTIVE: To evaluate the effect of disease-modifying antirheumatic drugs (DMARDs) on the likelihood of patients with rheumatoid arthritis (RA) developing septic arthritis (SA). METHODS: The United Kingdom General Practice Research Database (GPRD) was used to identify adults with RA, and age-, sex-, and practice-matched control subjects. Subjects were studied between 1987 and 2002. The risk of developing SA (excluding infected joint replacements) for individuals with RA was calculated and the effect of DMARD use determined. RESULTS: A total of 136,977 subjects (34,250 patients with RA, 102,747 controls) were identified. SA was identified in 345 subjects, of which 321 (236 in patients with RA, 85 in controls) cases occurred during the study period. The incidence rate of SA was 12.9 times higher in subjects with RA than in those without (95% confidence interval [95% CI] 10.1-16.5, P < 0.001). The incident rate ratios (IRRs) for developing SA while receiving DMARDs compared with receiving no DMARDs were different for different medications. Penicillamine (adjusted IRR 2.51, 95% CI 1.29-4.89, P = 0.004), sulfasalazine (adjusted IRR 1.74, 95% CI 1.04-2.91, P = 0.03), and prednisolone (adjusted IRR 2.94, 95% CI 1.93-4.46, P < 0.001) were associated with an increased incidence of SA when compared with not receiving any DMARD. The use of other DMARDs including methotrexate showed no such effect. CONCLUSION: Individuals with RA have an increased risk of developing SA. This increased risk can be attributed to both the disease process and the use of DMARDs.